دور معلم اللغة العربية في تطبيق التعليم الإلكتروني للفـصل الثامن بالمدرسة الثانوية الحكومية السادسة فونوروكو: THE ROLE OF ARABIC TEACHER IN E-LEARNING APLICATION FOR EIGHTH CLASS AT MTsN 6 PONOROGO - Riski Janu Saputra; Burhan Lukman Syah (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2022)
As the of Arabic language is important, it requires to be learned. To see the absorption of learners in Arabic language materials, researchers examined the role of Arabic teachers in e-learning in terms of material preparation, technology monitoring and motivation for improving their competencies And the purpose of this research: (1) knowing the school E-Learning learning preparation. (2) Knowing the role of Arabic teachers in E-Learning learning for grade 8 students in MTsN 6. And this research includes descriptive qualitative research.From the analyzed data, the results of the research can be known are: (1) The application of E-learning learning in MTsN 6 (a) This learning has been implemented starting from the new periode of 2020-2021, (b) Madrasah is using E-learning from the Ministry of Religious Affairs, (c) Madrasah has prepared tools for E-learning, (d) Learning in madrasah is intended in web based learning model, (e) learning in madrsah is an asynchronous learning , (f) the advantages of this learning are practical, and facilitated students, (g) the disadvantage of learning: expensive costs, large storage (2) The role of Arabic teachers in E-learning learning for grade 8 A in MTsN 6 (a) The role of Arabic teachers as constituents of materials by teaching the government material then it adjusted to the students' abilities and adding appropriate learning media. then for evaluation, more in a negative direction. (b) The role of Arabic teachers as technology builders by using madrasahs E-learning , which this application can be referred as madrasah online. The printed E-learning books, it is divided into 3 : MGBK, Module, and LKS. (c) The role of Arabic teachers as the motivator runs smoothly between the interaction of learners with the teachers, the students with E-learning, as well as learners with themselves, but there has not been any interaction among students itself. (d) The role of Arabic teachers in improving learners by conducting briefings and preactteks on the use of this learning, so there is a development of the students abilities for using this learning. Which is very appropriate to be used in the pandemic period.